Why airborne transmission hasn't been conclusive in case of COVID-19? An atmospheric science perspective - Ram K.; Thakur R.C.; Singh D.K.; Kawamura K.; Shimouchi A.; Sekine Y.; Nishimura H.; Singh S.K.; Pavuluri C.M.; Singh R.S.; Tripathi S.N. (My University, 2025)
Airborne transmission is one of the routes for the spread of COVID-19 which is caused by inhalation of smaller droplets1 containing SARS-CoV-2 (i.e., either virus-laden particulate matter: PM and/or droplet nuclei) in an indoor environment. Notably, a significant fraction of the small droplets, along with respiratory droplets, is produced by both symptomatic and asymptomatic individuals during expiratory events such as breathing, sneezing, coughing and speaking. When these small droplets are exposed to the ambient environment, they may interact with PM and may remain suspended in the atmosphere even for several hours. Therefore, it is important to know the fate of these droplets and processes (e.g., physical and chemical) in the atmosphere to better understand airborne transmission. Therefore, we reviewed existing literature focussed on the transmission of SARS-CoV-2 in the spread of COVID-19 and present an environmental perspective on why airborne transmission hasn't been very conclusive so far. In addition, we discuss various environmental factors (e.g., temperature, humidity, etc.) and sampling difficulties, which affect the conclusions of the studies focussed on airborne transmission. One of the reasons for reduced emphasis on airborne transmission could be that the smaller droplets have less number of viruses as compared to larger droplets. Further, smaller droplets can evaporate faster, exposing SARS-CoV-2 within the small droplets to the environment, whose viability may further reduce. For example, these small droplets containing SARS-CoV-2 might also physically combine with or attach to pre-existing PM so that their behaviour and fate may be governed by PM composition. Thus, the measurement of their infectivity and viability is highly uncertain due to a lack of robust sampling system to separately collect virions in the atmosphere. We believe that the present review will help to minimize the gap in our understanding of the current pandemic and develop a robust epidemiological method for mortality assessment. © 2021 Elsevier B.V.